Using Three-Tier Test to Identify the Quantity of Student that Having Misconception on Newton's Laws of Motion Concept - Emi Sulistri; Lisdawati Lisdawati (JIPF (Jurnal Ilmu Pendidikan Fisika), 2017)
This study aims to identify students quantity who are having the misconception on Newton's laws of motion concept using a Three-tiered Test. The sampling technique used in this study is purposive sampling technique and has been conducted on 56 students at Senior High School. A three-tier "Newton’s Law Of Motion Test" with 10 items is using as instrument to collected date in this study. The results showed that the quantity of students who experienced misconception with the highest category is on the concept of determining the relationship between the mass of objects and the time required for free fall that is equal to 89.3%. While the lowest category is in the concept of explaining the relationship between acceleration, mass and force with the time required for the object to fall freely that is equal to 26.8%.